Factors Associated with Headaches in Smartphone Users - Wahyuni, Erna Dwi; Faravida, Aulathivali Inas; Pratiwi, Ika Nur (International Journal of Psychosocial Rehabilitation, 2020)
The use of a smartphone has increased significantly and this can affect a person’s health, including the incidence of headaches. This study aimed to analyze the factors that can trigger the incidence of headaches in smartphone users. The design of this study was descriptive analytics with a cross-sectional approach. A simple random sampling technique was chosen to get respondents according to the inclusion criteria. The population was 704 college students in the Faculty of Nursing Universitas Airlangga, with a total number of respondents of 176 students. The independent variables were the duration of smartphone use, frequency of smartphone use, and radiation level of the smartphone that is used. The dependent variable was the incidence of headaches. The instrument used was a questionnaire about smartphone use and a questionnaire about headaches characteristics. The data were analyzed using Spearman’s Rank Correlation Coefficient with p = 0.05. The findings revealed a correlation between the duration of smartphone use (p = 0.000) and the incidence of headaches, so is the frequency of smartphone use (p = 0.004). And there was no correlation between the radiation level of the smartphone that is used (p = 0.978) and the incidence of headaches. The factors that can increase the incidence of headache in smartphone users were the duration and frequency of smartphone use.